Respuesta :

Answer:

[tex]m=5[/tex]

Step-by-step explanation:

The average rate of change m of a function is calculated using the following formula

[tex]m=\frac{f(x_2)-f(x_1)}{x_2-x_1}[/tex]

In this case we look for the average exchange rate between [tex]x = 0[/tex] and [tex]x = 2[/tex].

Therefore we must find [tex]f(2)[/tex] and [tex]f(0)[/tex]

You can see in the graph that when [tex]x = 2[/tex] then [tex]y = 11[/tex]

therefore [tex]f(2) = 11[/tex]

You can see in the graph that when [tex]x = 0[/tex] then [tex]y = 1[/tex]

therefore [tex]f(0) = 1[/tex]

Finally

[tex]m=\frac{f(2)-f(0)}{2-0}[/tex]

[tex]m=\frac{11-1}{2-0}[/tex]

[tex]m=\frac{10}{2}[/tex]

[tex]m=5[/tex]

Answer:

whats the correct answer: 4, 5, 10 or 11?